SMART BUS TRANSPORT SYSTEM USING GSM AND GPS - GAIKWAD PARMESHWAR; RAUT ANAND; BAGAL TEJASHREE (International Journal of Innovations in Engineering Research and Technology, 2021)
It is the major problem for everyone. In this present scenario, we are designing a GPS-GSM based system which identifies bus exactly at which location it has started recently. For this purpose here we are using GSM-GPS connected to the bus. The project implements solution for enhancing public transportation management services based on GPS and GSM .In this system the message is send to the passenger who are waiting for the that bus when the bus is leave previous station. In this system the passengers are countedautomatically